(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The entire society knows Scavengers, Safai Karamcharis and that their dependants are living a melancholy life. But very few of them are knows about its cause of reality. Our legislation has given them profuse source to live with purity. In every situation they proved to themselves how much Nation waiting to them. Swachh Bharat Mission Pandemic COVID-19 is the best example of this Century. Safai Karamcharis are very kind-hearted and innocent. Their involvement in demeaning and despicable occupation is not perfunctory rather their involvement is to get salvation from starvation and minimum trial for better living. Their service always dedicated to the society for a noble cause. They respect to their employer like incarnation of God. They never calculate their employer’s merits and demerits as because they know if they will go against the employer definitely their entire family will remain in starvation. The object to write this Article is to unveil the bare facts of petty or we can poorly conditions of the Scavengers despite of all efforts made by the concerned authorities in India at all Legislative, Administrative and Judicial levels.